A literature survey of post-translational modification on lysine. - Tan, Li. (2012)
Lysine acetylation and methylation has emerged as major post-translational modifications (PTMs) for proteins in eukaryotic cells. They are highly dynamic and reversible, contributing to a complex network that modulates chromatin dynamics as well as other important cellular activities. Various special domains, including bromodomain and chromodomain, can recognize the modified lysines and interact with them, providing a mechanism to “read” the PTMs. PTMs frequently target large complexes as substrates, and they are able to crosstalk to each other. They are correlated with various diseases such as cancers and neurological disorders. Some specific PTMs have been found to be essential for onset of diseases, thus the enzymes responsible for lysine acetylation and methylation has considered as potential drug targets. This review summarizes all the known enzymes involved in lysine acetylation and methylation, their functional impacts, and their implication in diseases.